2022
DOI: 10.3389/fneur.2022.866983
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Therapeutic Approaches for the Treatment of Retinal Pathology in Neuronal Ceroid Lipofuscinoses

Abstract: The neuronal ceroid lipofuscinoses (NCLs) are a group of childhood-onset neurodegenerative lysosomal storage disorders mainly affecting the brain and the retina. In the NCLs, disease-causing mutations in 13 different ceroid lipofuscinoses genes (CLN) have been identified. The clinical symptoms include seizures, progressive neurological decline, deterioration of motor and language skills, and dementia resulting in premature death. In addition, the deterioration and loss of vision caused by progressive retinal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Prior investigations have highlighted glial dysfunction in NCL murine models coinciding with subsequent neuronal damage of the visual cortex and retina, resulting in deterioration of visual perception and retinal function [48][49][50]. Moreover, attenuation of inflammatory microglia via therapeutic agents in Batten disease animal models improved visual acuity, reduced retinal thinning, and improved retinal ganglion cell survival [49,[51][52][53]. Sex comparisons of microglia contribution to pathology and response to therapy in vision related systems may better elucidate this process.…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigations have highlighted glial dysfunction in NCL murine models coinciding with subsequent neuronal damage of the visual cortex and retina, resulting in deterioration of visual perception and retinal function [48][49][50]. Moreover, attenuation of inflammatory microglia via therapeutic agents in Batten disease animal models improved visual acuity, reduced retinal thinning, and improved retinal ganglion cell survival [49,[51][52][53]. Sex comparisons of microglia contribution to pathology and response to therapy in vision related systems may better elucidate this process.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using animal and cell model systems of CLN3 disease have shed light on a wide range of roles that CLN3 protein may participate in, including: intracellular trafficking [3][4][5][6] , autophagy [7][8][9] , Ca 2+ levels 10 , lysosomal egress 11 , and lysosomal pH 12 . However, the exact pathway(s) that CLN3 is involved in are still debatable, which may contribute to the lack of treatments for this disease despite of current development of potential interventions such as gene therapy 13,14 . Clinically, the most common (in 80% of patients) and often an early symptom is functional vision loss, the onset of which occurs around 5-6 years of age 15 .…”
Section: Cln3 Diseasementioning
confidence: 99%
“…Our characterization of sleep in a mouse model of CLN3 disease contributes to a better understanding of the sleep disturbances commonly reported for CLN3 disease and other NCLs, which will facilitate the development of new disease treatment and management strategies. therapy 13,14 . Clinically, the most common (in 80% of patients) and often an early symptom is functional vision loss, the onset of which occurs around 5-6 years of age 15 .…”
mentioning
confidence: 99%
“…Currently, there are no available treatments to alleviate clinical symptoms for the majority of Batten disease. 8 , 9 In the case of CLN2 Batten disease, research studies have shown that a recombinant human tripeptidyl peptidase-1 (TPP1) can be delivered into the cerebrospinal fluid every two weeks. 10 , 11 , 12 , 13 While positive results have been seen with this form of enzyme replacement therapy, it has a high incremental cost-utility ratio and the frequent delivery causes distress for paediatric patients.…”
Section: Introductionmentioning
confidence: 99%